Open Right Hemicolectomy Is a Safe and Suitable Procedure for Surgical Training: A Comparative Study With 133 Patients. (June 2018) - Hirche, Z.; Zabaka, K.; Hirche, C.; Xiong, L.; Willis, S.
Background and Aims: A right hemicolectomy is a technically demanding procedure and the quality of the operation influences the short- and long-term outcomes. An increasing number of certified centers employ surgeons who are specialized in this procedure. Residency training is obligatory, but trainee surgeons often cannot perform technically demanding procedures because of economical and certification requirements imposed on the center. This study was performed to evaluate the suitability of right hemicolectomy as a training procedure. Material and Methods: Between 2009 and 2013, 133 patients received a right hemicolectomy during cancer treatment. Patient data were analyzed in two cohorts: cohort 1 contained 90 patients who were operated by a resident under supervision, and cohort 2 included 43 patients who were operated by a specialized senior surgeon. Outcome and safety were evaluated by mortality rate, anastomotic leakage, complication rate, and operation time. The resection status and the number of resected lymph nodes were surrogate parameters for oncological quality. Gender, age, American Society of Anesthesiologists classification, body mass index, and general risk factors were compared in both cohorts. Results: There was no significant difference in the rate of anastomotic leakage between the two groups (p = 0.799). Oncological criteria were met in both cohorts and the oncological quality was similar between groups. Furthermore, there were no significant differences in risk factors, operating time, postoperative complications, and mortality between the groups. Conclusion: Oncological open right hemicolectomy is a safe and suitable training procedure for residency training under standardized conditions.